2016
DOI: 10.1007/s00216-016-9532-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical biosensing of galactose based on carbon materials: graphene versus multi-walled carbon nanotubes

Abstract: In this study, two enzyme electrodes based on graphene (GR), Co3O4 nanoparticles and chitosan (CS) or multi-walled carbon nanotubes (MWCNTs), Co3O4 nanoparticles, and CS, were fabricated as novel biosensing platforms for galactose determination, and their performances were compared. Galactose oxidase (GaOx) was immobilized onto the electrode surfaces by crosslinking with glutaraldehyde. Optimum working conditions of the biosensors were investigated and the analytical performance of the biosensors was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 52 publications
2
25
0
1
Order By: Relevance
“…The fast electron transfer ability, excellent thermal conductivity, strong mechanical strength and biocompatibility make the GR a promising material for biosensing applications . Graphene based biosensors generally show higher sensitivities and a lower detection limits than conventional carbon electrode based biosensors , . For these reasons, graphene is regarded as an ideal material to fabricate high performance biosensors.…”
Section: Introductionmentioning
confidence: 49%
“…The fast electron transfer ability, excellent thermal conductivity, strong mechanical strength and biocompatibility make the GR a promising material for biosensing applications . Graphene based biosensors generally show higher sensitivities and a lower detection limits than conventional carbon electrode based biosensors , . For these reasons, graphene is regarded as an ideal material to fabricate high performance biosensors.…”
Section: Introductionmentioning
confidence: 49%
“…9 GO is also an important component in electrochemical biosensors of galactose that are used for various biotechnology applications. 1012 Despite accomplishing 2e − reduction of O 2 , the active site of GO contains only a single Cu. To provide the additional redox equivalent required for turnover, the active-site Cu is coordinated by a unique cysteinylated tyrosine (Cys-Tyr) ligand that serves as a second redox-active cofactor.…”
Section: Introductionmentioning
confidence: 99%
“…Further we compared published GaOx based systems with our proposed system based on PyOx‐MTs, acceptable and comparable results were found (Table ). For example Tkac et al., in their study suggested single walled carbon nanotubes dispersed in a chitosan matrix using GaOx for the design of a galactose biosensor .…”
Section: Resultsmentioning
confidence: 99%